2015
DOI: 10.1111/are.12869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary vitamin C on the growth performance, antioxidant ability and innate immunity of juvenile yellow catfish (Pelteobagrus fulvidracoRichardson)

Abstract: A 12-week feeding trial was conducted to evaluate the effects of dietary vitamin C on growth performance, antioxidant status and innate immune responses in juvenile yellow catfish, Pelteobagrus fulvidraco. Six isonitrogenous and isolipidic diets (44% crude protein and 7% lipid) were formulated to contain six graded dietary vitamin C (ascorbate-2-poly-phosphate, ROVIMIX â STAY-C â 35) levels ranging from 1.9 to 316.0 mg kg À1 diet. The results of present study indicated that fish fed the lowest vitamin C diet h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 41 publications
13
69
0
4
Order By: Relevance
“…Recently, yellow catfish ( Pelteobagrus fulvidraco Richardson) fed the diets supplemented with vitamin C had higher SOD, CAT and GPX activities than those fed vitamin C‐deficient diet (Liang et al . ). Similar studies demonstrated that dietary vitamin C has a positive effect on antioxidant capacity of Siberian sturgeon (Xie et al .…”
Section: Vitamins C (Aa) and E (α‐Tocopherol α‐Toc) As Antioxidant Amentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, yellow catfish ( Pelteobagrus fulvidraco Richardson) fed the diets supplemented with vitamin C had higher SOD, CAT and GPX activities than those fed vitamin C‐deficient diet (Liang et al . ). Similar studies demonstrated that dietary vitamin C has a positive effect on antioxidant capacity of Siberian sturgeon (Xie et al .…”
Section: Vitamins C (Aa) and E (α‐Tocopherol α‐Toc) As Antioxidant Amentioning
confidence: 97%
“…; Lin & Shiau ,b; Kim & Kang ; Liang et al . ), mucosal immune response (Roosta et al . ), haematology (Shahkar et al .…”
Section: Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that dietary vitamin C could improve the antioxidant capacities in Pacific abalone Haliotis discus hannai Ino (Wu, Wang, Xu, Zhang, & Mai, 2014) and red sea bream Pagrus major (Gao et al, 2013). A similar study in yellow catfish Pelteobagrus fulvidraco suggested that the activities of serum superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) significantly increased when dietary L-ascorbic acid levels increased from 1.9 to 156.5 mg/ kg (Liang, Li, Hou, Qiu, & Zhou, 2015). Chen et al (2015) also reported that vitamin C supplementation significantly increased CAT activity, reduced glutathione content and total antioxidant capacity (T-AOC) in the liver and muscle of largemouth bass Micropterus salmoides.…”
mentioning
confidence: 94%
“…However, in recent years, several nutritional requirements have been reported about this crustacean such as shrimp and prawn including some vitamins requirements such as vitamin C (Vc) and E (Cavalli et al, 2001(Cavalli et al, , 2003Sealey and Gatlin, 2002;Liang et al, 2015;Wang and Huang, 2015;Chen et al, 2015). Furthermore, there is no information about antioxidant effect and serum biochemistry parameters of folic acid on M. rosenbergii which are important factors affecting prawn's health.…”
Section: Introductionmentioning
confidence: 99%